Edaphic characteristics of soddy-lithogenic soil on grey-green сlays on the basis of environmental micromorphology - Кацевич, В. В.; Грицан, Ю. І. (Scientific Progress & Innovations, 2018)
In general, in Ukraine the rate of land alienation with the purpose of mining operations is far ahead of the rate of reclaimed areas recovery. As a result, the problem of disturbed lands reclamation and their returning to economic use becomes a high priority state problem. The objective of our study was characterizating the pegogenesis of soddy-lithogenic soil onto grey-green сlay in the condition of land reclamation of the Research-Experimental Agrarian Station of Dnipro State Agrarian-Economic University (DSAEU). According to the results of micromorphological study of soddy-lithogenic soils onto grey-green сlay conducted at DSAEU Research-Experimental Agricultural Station near Pokrov city, Nikopol district of Dnipropetrovsk region, agroecological substantiation of pedogenesis was presented. The peculiarities of the micromorphological structure of technozem on the experimental plot of agricultural reclamation were studied. It was established that the dominance of carbonates is common in each soil horizon. Due to effect of climatic and biological factors, calcareous neoformations in the topsoil are much smaller in size in comparison with subsoil, and the number of large ones is negligible. With the depth, the effect of weathering decreases, leading to much larger size of calcareous neoformations. Micromorphological studies show that fine-grained calcite was the most common type of neoformations in the soil profile, which saturates the material with bases, and its mottles in pores. It was determined that organic substance was contained mainly in the upper soil horizons 20 cm deep. It is mainly represented by black humus, gumones and fresh plant residues. The absence of the intermediate stages of fresh plant residues decomposition provides the evidence of a high rate of organic matter decomposition.